Faces and places - Nayyar, Deepak (New Delhi Roli Books, 2015)
Faces and Places This book brings together a selection of the authors photographs that have been taken over the past four decades. Some go back even longer in time. It is a book of pictures, in terms of attractive visuals for the reader to be engaged, simply by turning the pages, but not quite in a conventional sense. These photographs are about the world around us. In fact, its title captures the essential idea of its dual theme. The focus is on people in their daily lives and on places that are of interest to visitors.
Keywords: Photographs - human diversity